2005
DOI: 10.1016/j.jcrs.2005.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of endothelial cell decrease with VisThesia in phacoemulsification surgery

Abstract: The results observed in this investigation indicate that the addition of lidocaine to the sodium hyaluronate in VisThesia does not induce additional toxicity nor does it result in increased endothelial cell loss when compared with other, similar OVDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
2
17
1
Order By: Relevance
“…10 Although our results showed more central endothelial cell loss at 1 year with MICS than with coaxial phacoemulsification, we believe MICS is a safe and reliable technique, not only because there was no difference in the visual outcomes between the groups but also because the central endothelial cell loss was within the acceptable and safe rate cited in the literature with coaxial phacoemulsification. [28][29][30] In conclusion, MICS required more US time than coaxial phacoemulsification; however, the mean US power was the same in the 2 groups. The BCVA was also similar in between the groups.…”
Section: Discussionmentioning
confidence: 76%
“…10 Although our results showed more central endothelial cell loss at 1 year with MICS than with coaxial phacoemulsification, we believe MICS is a safe and reliable technique, not only because there was no difference in the visual outcomes between the groups but also because the central endothelial cell loss was within the acceptable and safe rate cited in the literature with coaxial phacoemulsification. [28][29][30] In conclusion, MICS required more US time than coaxial phacoemulsification; however, the mean US power was the same in the 2 groups. The BCVA was also similar in between the groups.…”
Section: Discussionmentioning
confidence: 76%
“…Randomized trials found that intracameral lidocaine 1% used as a supplement to topical anesthesia may slightly reduce patients discomfort and may not be toxic to the corneal endothelial cells when applied once prior to capsulorhexis (Carino et al 1998; Garcia et al 1998; Tseng and Chen 1998; Gillow et al 1999). As for VisThesia ® , Poyales-Galan and Pirazzoli (2005) reported corneal endothelial cell loss comparable to that reported for similar OVDs, whereas Perone et al (2007) reported worse corneal endothelial protection than with DuoVisc ® (VIscoat ® plus ProVisc ® ) suggesting lidocaine 1% may be toxic when used as an ingredient of OVDs. Removal properties of VisThesia ® should be similar to those of sodium hyaluronate 1.5% because a mixture of lidocaine 1.0% with sodium hyaluronate 1.5% does not significantly alter its removal time from the capsular bag of postmortem human eyes (Pandey 2003).…”
Section: New Generation Of Sodium Hyaluronate Agentsmentioning
confidence: 69%
“…In fact, the literature provides conflicting evidence regarding the potential cytotoxic role of lidocaine hydrochloride 1% on endothelial cells. While Poyales-Galan and Pirazzoli [18] in their report suggested no additional cytotoxic effect of Visthesia, Perone et al [19] indicated a significant impact on ECC when using Visthesia. Moreover, Moschos et al reported an ECC reduction of 9.6% in their Visthesia group of cataract patients [20].…”
Section: Discussionmentioning
confidence: 97%